2019
DOI: 10.32394/rpzh.2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of metabolic indicators for cardiovascular risk in schoolchildren

Abstract: Objective. CardioVascular Disease (CVD) is one of the most important causes of death worldwide affecting people at younger ages every year. The purpose of this study was to identify the metabolic indicators for cardiovascular risk factors in primary school students from Mexico and Colombia. Methods. A clinical, prospective, cross-sectional and comparative study was conducted in Mexico and Colombia to contrast anthropometric measurements, biochemical and dietetic determinations and physical activity. Results. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Las causas por las cuales el resto de artículos fueron omitidos son: 1) investigaciones no realizadas específicamente en Colombia: [14], [15] [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28, [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46] y [47]. 2) No tenían en cuenta la AF o ejercicio como tema principal o no eran investigaciones: [48], [49], [50], [51], [52], [53], [54] [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], …”
Section: Resultsunclassified
“…Las causas por las cuales el resto de artículos fueron omitidos son: 1) investigaciones no realizadas específicamente en Colombia: [14], [15] [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28, [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46] y [47]. 2) No tenían en cuenta la AF o ejercicio como tema principal o no eran investigaciones: [48], [49], [50], [51], [52], [53], [54] [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], …”
Section: Resultsunclassified
“…The predictability of ABSI and other anthropometric parameters for chronic diseases and all-cause mortality may not be uniformly distributed across population subgroups. WHR and WtHR showed significant differences between Mexico and Colombia [33]. A study conducted among a European population showed that waist circumference and WHR are stronger predictors for cardiovascular mortality than BMI and ABSI [40].…”
Section: Abbreviations: N -Number Of Participants; Bmi -Body Mass Indmentioning
confidence: 96%